Midwifery Care for Pregnant Women in the Third Trimester with the Obstetric Complaint of Low Back Pain - Bella Novelia Putri; Desy Dwi Cahyani; Finta Isti Kundarti (KHD Production, 2025)
Low back pain is a common musculoskeletal disorder experienced during pregnancy, with a prevalence ranging from 30% to 78% in regions such as the United States, Europe, and Africa. Approximately one-third of affected individuals experience low back pain that leads to decreased productivity and reduced quality of life. An increased body weight of 11–12 kg, along with hormonal and biomechanical changes during pregnancy, contributes to a higher risk of pain in the back, pelvis, and other musculoskeletal areas. Given the potential impact of such complications during pregnancy, health policymakers should place greater emphasis on addressing this issue. In addition, public education on the importance of maternal health, coupled with timely diagnosis and intervention efforts, plays a crucial role in reducing pregnancy complications. This study aims to provide midwifery care to a third-trimester pregnant woman with complaints of low back pain through a case study of Mrs. N.A. (G3P2002, 28 weeks gestation). Data were collected through interviews, observation, physical examination, and documentation review. Diagnoses were made based on subjective and objective findings, and interventions were implemented through health education and pregnancy gymnastics as a promotive and preventive approach to improving maternal well-being. The evaluation results showed a significant improvement in the client's lower back pain after the intervention. The client reported decreased pain intensity to the point where it no longer interfered with daily activities, indicating that the intervention was effective and aligned with the previously planned objectives and success indicators. It is essential to provide follow-up education and regular evaluations in midwifery practice to ensure that similar complaints do not recur or develop into more serious issues.